The Impact of Career Guidance Service Quality at the German Agency for International Cooperation on Service Recipients’ Satisfaction: The Role of Career Counselors as Mediating Factors, in Jordan - Harazneh, Amer Abdelqader (European Scientific Journal, ESJ, 2024)
This exploratory research study aims to comprehensively understand and analyze service recipients’ overall satisfaction with their career counseling experience at the German Agency for International Cooperation in Jordan. The evaluation of this service varied significantly based on the diverse socio-demographic information collected from participants. Furthermore, the perceived quality of the career guidance service emerged as the most significant factor directly influencing the overall satisfaction levels of service recipients. The study is based on quantitative approaches to the data collection process, a mixture of research methods. The structural model was examined in two stages. In the first stage (direct effect) the effect (QOS→ ECC) was significant (table 4 ), therefore H1 was supported, also effect was significant about (ECC→STA), hypotheses 2 was supported, (QOS→ STA) was not significant so hypotheses 3 were not supported. To the best of our knowledge, this study is the first to investigate whether career counselors who work at the GJU-CoB-CDC are mediating factors that can affect the relationship between career guidance service quality and the satisfaction of GJU-CoB-CDC service recipients.